2022
DOI: 10.1002/slct.202104270
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Novel Thiazole Analogs with Both Anti‐Proliferative and Mechanistic Analyses and Molecular Docking Studies

Abstract: Herein, we report the synthesis of a novel series of βhimachalene derivatives, including semicarbazones, thiosemicarbazones, and thiazoles. The structures of these compounds were elucidated by NMR, IR, and HRMS analysis methods. The in vitro antitumor activity of these compounds was evaluated by the MTT assay against four human cancer cell lines, such as fibrosarcoma (HT-1080), breast adenocarcinoma (MCF-7 and MDA-MB-231), and lung carcinoma (A-549), and the results indicated that all compounds showed moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 51 publications
(46 reference statements)
1
2
0
Order By: Relevance
“…These results indicate that these compounds possess a considerable and selective cytotoxic activity toward breast cancer cell lines, with a low cytotoxic effect on the epithelial breast cells. Our results are in accordance with previously reported studies, which showed that 1,3-thiazole compounds are potent antiproliferative agents [ 48 , 49 , 50 , 51 , 52 , 53 ]. Among different investigated compounds, compounds 3c and 4 demonstrated the most potent anticancer activity toward the examined MCF-7 breast cancer cell line, with an IC 50 = 13.66 µM and 5.73 µM, respectively, compared to STU, with anIC 50 of 6.77 µM ( Figure 4 ).…”
Section: Resultssupporting
confidence: 94%
“…These results indicate that these compounds possess a considerable and selective cytotoxic activity toward breast cancer cell lines, with a low cytotoxic effect on the epithelial breast cells. Our results are in accordance with previously reported studies, which showed that 1,3-thiazole compounds are potent antiproliferative agents [ 48 , 49 , 50 , 51 , 52 , 53 ]. Among different investigated compounds, compounds 3c and 4 demonstrated the most potent anticancer activity toward the examined MCF-7 breast cancer cell line, with an IC 50 = 13.66 µM and 5.73 µM, respectively, compared to STU, with anIC 50 of 6.77 µM ( Figure 4 ).…”
Section: Resultssupporting
confidence: 94%
“…The YASARA dynamics version 18.4.24.W.64 simulations were carried out with MD. [ 52 ] They were run in an explicit water environment for 137 ns, using the AMBER‐14 force field with constant pressure and simulated temperature of 298 K. For the first time, a MD simulation has been performed at constant temperatures and pressures for 137 ns following a balance, and MD trajectory snapshots were kept every 100 ppm for subsequent examination for a duration of 2 ns. MD simulations include RMSF, root‐medium‐square deviation (RMSD), radon (Rg), solvent surface accessible (SASA), and RMSD ligand motion when overlaid on the receiver.…”
Section: Methodsmentioning
confidence: 99%
“…Also, they are considered as starting material for the development of new drugs especially anti-cancer agents. For this reason, many compounds with anticancer activity have been designed by hybridization, bearing at least two or more pharmacophores in one chemical structure [1][2][3][4][5][6] Hybrid molecules incorporating five membered nitrogen and oxygen containing heterocycles were found to be particularly effective in terms of enhancing biological activities, when compared to that of individual pharmacophores. [7][8][9] These heterocycles include triazoles and isoxazoles which are absolutely a major class of nitrogen and oxygen containing five-membered heterocycles in drug design.…”
Section: Introductionmentioning
confidence: 99%